Somatic Embryogenesis and Plant Regeneration in Ephedra foliata (Boiss.); a non Coniferous Gymnosperm (Plant Tissue Culture and Biotechnology, 2011)
Embryos from mature seeds of Ephedra foliata were excised and used as explant after longitudinal splitting. Half embryos were cultured in vitro to assess their morphogenic potential. When 2 - 10 µM  2,4-D with 2 - 10 µM Kn was used in MS with 10% coconut milk callus, roots and somatic embryos were induced. Lower concentration of 2 and 5 µM 2,4-D with 2 to 15 µM Kn gave best responses in terms of percentage of cultures showing somatic embryos. greater degree of callusing was obtained in a combination of 8 - 10 µM 2,4-D with Kn, but frequency of somatic embryos was low. Substituting BAP for Kn in the medium containing 2,4-D showed almost the same response as that in 2,4-D and Kn. The percentage of cultures showing root formation was low as compared to Kn combinations. Somatic embryos developed, but with a lesser frequency. When different concentrations of NAA were added with Kn, only rooting and callusing occurred. On this medium, there was a total absence of somatic embryos. When somatic embryos were transferred to a hormone free medium, they grew within 10 - 15 days. The fully grown somatic embryos then germinated and developed into plantlets. Chromosomal count confirmed retention of ploidy level.  Plantlets from somatic embryos were transferred to pots containing sterilized mixture of coarse sand and garden soil in equal proportions. They survived well and formed new nodes and internodes after nearly one month.   Key words:  Ephedra, Somatic embryogenesis, Micropropagation, Ephedrine   D.O.I. 10.3329/ptcb.v20i2.6893   Plant Tissue Cult. & Biotech. 20(2): 133-143, 2010 (December)